The pragmatic orientation of figurative comparisons in works of Lina Kostenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article investigates the figurative comparisons, that are discovered in works of Lina Kostenko. Their semantic, formal-grammatical and pragmatic features are analyzed. An attempt to systematize the comparisons with according to representation of reflected types is made. The features of actualization of the proper information, which are coded in figurative comparisons, are studied.
Keywords: figurative comparisons; semantics; formal structure; character; attribute; type; pragmatic orientation